Information Communication Technology (ICT) among University Students in Pakistan - Mumtaz, Lama; Ali, Mujahid; Fatima, Ambreen; Shaikh, Faiza (Pakistan Journal of Humanities and Social Sciences, 2023)
In the sphere of education, the influence of technology is growing tremendously. However, due to rapid technical progress, its implementation has been fraught with various difficulties, particularly in developing countries. This study investigates current trends and challenges in the use of information and communication technology (ICT) among university students in Karachi, Pakistan. The study is based on a quantitative approach. A random sample of 130 university students is collected through a paper-pencil survey questionnaire. For data analysis, descriptive statistics are applied. According to the results, the majority of students use smartphones for educational purposes and spend more time on the internet for entertainment and other purposes than for academic purposes. They acknowledge the significant role of technology in their learning and have an intermediate level of computer skills. Most of the students are dissatisfied with the available ICT-based technology in universities.